Jurisdição e poder de enunciação fática: a normalização nos interstícios do agir jurisdicional - Mello Neto, Carlos Pessoa de (2009)
This study titled "Jurisdiction and the power of fact enunciation: normalization in the interstices of the court act" aims to get close to the performance of magistrates and courts of the judiciary power (the court action), specifically in its activities related to the creation of official versions of facts. From the assumption that such activity is based on a specific state power, called in this study the power of fact enunciation, we will show that the court actions are composed by other powers required for its performance. Given this diversity of powers, this study questions what kind of authorities and what kind of legitimization procedures the society is subjected to, specifically the citizens in courts. Based on a critical-dualistic methodology, which divides facts and decisions, balanced by the theory of speech acts, from Searle, this study will try to understand the various forms of ilocucionary strength, which affect the court actions. In this direction, after questioning the means of justification for the judicial activity and verification of its legitimacy, this study will seek to understand the idea of modalization explained by a linguistics enunciation, which will be used to explain how to carry out normalization, found inside the State, in its court action. However, it should be highlighted that this study, although closer to the theory of speech acts, believes that it is possible to match this ideas with the critical dualism and with the theory of truth as correspondence. Finally, this study results in a theoretical discourse related not only to the needs to legitimize the normative activity in a Republican state (in the way of Arendt), and democracy, but also to the activity related to the creation of official versions for past happenings, through the power of the fact enunciation